Analisis Struktur Dan Komposisi Kimia Pada Tahapan Evolusi Bintang Primer Bermassa 2.24M_⊙Tipe Algol - M. Abu Kamal; Asih Melati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Modeling has been carried out using the STARS software to analyze the structure and chemical composition of a primary star with a mass of 2.24M_⊙ type Algol. Algol type stars are close binary star systems that experience the Algol pradox. The Algol paradox is a situation where a star with a smaller mass turns out to have evolved further than a star with a larger mass. The results of this modeling are (1) HR diagrams (2) star structure graphs and (3) graphs of star chemical composition as a function of radius.